2008
DOI: 10.1007/s12078-008-9030-4
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Salty Taste Stimulus Concentrations in the Primary Gustatory Area in Humans

Abstract: The relationship between neuronal activity in the human gustatory cortex and the concentrations of taste stimuli is not well understood. In this study, we recorded changes in the magnetic fields of the human brain in response to four concentrations of NaCl (30 mM, 100 mM, 300 mM, and 1 M) and measured the magnitude and shortest latency of the equivalent current dipole (ECD) in the primary gustatory area of the cerebral cortex (PGA). The average magnitude of ECDs in the PGA increased in a concentration-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
2
12
1
Order By: Relevance
“…The significant clusters in anterior insula reported in this study were close to the clusters previously reported for valence involvement (Dalenberg, Hoogeveen, Renken, Langers, & ter Horst, ; Jabbi, Swart, & Keysers, ; Small et al., ). Similarly, the significant clusters in middle insula reported in this study were close to the ones previously reported for processing intensity/ concentration (Kobayakawa, Saito, Gotow, & Ogawa, ; Small et al., ; Spetter, Smeets, de Graaf, & Viergever, ).…”
Section: Discussionsupporting
confidence: 91%
“…The significant clusters in anterior insula reported in this study were close to the clusters previously reported for valence involvement (Dalenberg, Hoogeveen, Renken, Langers, & ter Horst, ; Jabbi, Swart, & Keysers, ; Small et al., ). Similarly, the significant clusters in middle insula reported in this study were close to the ones previously reported for processing intensity/ concentration (Kobayakawa, Saito, Gotow, & Ogawa, ; Small et al., ; Spetter, Smeets, de Graaf, & Viergever, ).…”
Section: Discussionsupporting
confidence: 91%
“…With EEG, the effect of concentration on both the gERP's amplitude and latency has been reported for acetic and citric acids (Kobal, 1985; Hummel et al, 2010) but not for MSG and NaCl (Singh et al, 2011). Three MEG studies using NaCl reported effects of concentration on amplitudes and reaction times (Saito et al, 1998; Kobayakawa et al, 2008, 2012) but failed to observe an effect on latencies. Many factors can account for these inconsistencies such as the number of participants, of repetitions and of electrodes, as well as stimulus concentrations and presentation paradigm (same block or separately).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it has been suggested that the concentration of a tastant is signaled by the firing rate of taste-responsive cells (Ganchrow and Erickson 1970; Scott and Perrotto 1980), resulting in an increase of the amplitude of the evoked potential at the scalp. However, previous attempts to investigate the effects of taste intensity yielded inconsistent findings in that shorter latencies and higher amplitudes were observed when the concentration of acetic acid was increased (Hummel et al 2010), while increases in salt concentration led to augmented amplitudes only (Saito et al 1998; Kobayakawa et al. 2008).…”
Section: Gustatory Event-related Responsesmentioning
confidence: 92%